2016
DOI: 10.1017/s1742758416000023
|View full text |Cite
|
Sign up to set email alerts
|

Habitat and dung preferences of scarab beetles of the subfamily Scarabaeinae: a case study in a tropical monsoon forest in Sri Lanka

Abstract: We studied the food and habitat preferences of beetles of the subfamily Scarabaeinae in a protected tropical monsoon forest, the Wasgomuwa National Park in Sri Lanka. While gaining an insight into the capacity of different resources to support dung beetles, we tested the hypothesis that, in a landscape with a mosaic of habitat types and a diversity of large mammals, specialization facilitates coexistence of the scarabs. Pitfall traps were laid in five distinct habitat types (forest, riverine, sandy banks, scru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…, 67 species, H 2 ′ = 0.12), and communities with low diversity but with high specificity (Hewavithana et al . , 22 species, H 2 ′ = 0.41). Across the gradient in dung beetle diversity, the degree of specialisation was similar (Fig b).…”
Section: Discussionmentioning
confidence: 96%
“…, 67 species, H 2 ′ = 0.12), and communities with low diversity but with high specificity (Hewavithana et al . , 22 species, H 2 ′ = 0.41). Across the gradient in dung beetle diversity, the degree of specialisation was similar (Fig b).…”
Section: Discussionmentioning
confidence: 96%
“…Jaguar dung was the least preferred dung type by two species in the choice experiment, and field studies have also found carnivore dung to be the least attractive (Bogoni & Hernández, ; Hewavithana et al ., ). Adult dung beetles require liquid to filter‐feed high‐nutrient particles from dung, and the low moisture content of carnivore dung could explain the avoidance by some species (Al‐Houty & Al‐Musalam, ; Frank et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Estudios previos, llevados a cabo en el Bosque Atlántico, han explorado la influencia de la cobertura de dosel arbóreo, condiciones microclimáticas y presencia de ganado en respuesta a las perturbaciones de origen antrópico (Hernández et al, 2014;da Silva y Hernández, 2016;Bogoni et al, 2014;Gómez-Cifuentes et al, 2017); sin embargo, hasta el momento no se habían realizado estudios que pusieran a prueba todos los factores juntos, ni tampoco estudios que evaluaran si los cambios en Un gran número de estudios han mostrado que el reemplazo, la fragmentación y la degradación de los bosques tropicales y subtropicales cambian la abundancia (Sánchez-de-Jesús et al, 2016), riqueza y composición de especies (Halffter y Arellano, 2002;Scheffler, 2005;Nichols et al, 2007;Gardner et al, 2008;Neita y Escobar, 2012;Peyras et al, 2012;Audino et al, 2014;Hernández et al, 2014;Gómez-Cifuentes et al, 2017). En general, la magnitud de esos cambios ha sido asociada con la pérdida de recursos tróficos, como estimación indirecta a partir de la pérdida de grandes mamíferos, y con los cambios en las condiciones ambientales (Nichols et al, 2007;Hernández et al, 2014;Hewavithana et al, 2016;Gómez-Cifuentes et al, 2017). Los resultados de este trabajo concuerdan con los obtenidos por Alvarado et al (2018) en los cuales se obtuvo también que la pérdida de cobertura de dosel arbóreo es el factor que más influye en los cambios de diversidad, seguido por la presencia de ganado.…”
Section: Discussionunclassified